Analisis Penentuan Kadar Vitamin C (Asam Askorbat) Pada Obat VIT C 1000 Yang Beredar Di Kota Makassar - Haryanto Haryanto; Nabilah Syahrida; Suci Kurnia Salamah; Ayu Fatmasari; Dahyatul Qalbi; Andi Syarifah Reski Ayu Amelia Asyari; Fadhila Indah; Sindy Amaliah; Khusnul Khatimah A. Syahrir; Nur Hikmah Aulia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Vitamin C comes from fresh fruits and vegetables, which are sources of water-soluble vitamins. It is recommended for adults to consume 30-100 mg of vitamin C daily, but the need will vary from person to person. Both classical wet methods and instrumental methods can be used to determine the levels of ions. According to some studies, the iodometric titration method and sample content analysis can be used to determine the levels of anions. This study found that iodometric titration relies on the reaction between iodine as a titrant and a substance that has a lower oxidation potential than titration with starch (indicator). As a result of determining the level of ascorbic acid (vitamin C) with the sample "Vit C 1000", the result was 91.31%.